2014
DOI: 10.1159/000368049
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost-Effectiveness of Immediate Surgery versus a Wait-and-See Strategy for Sporadic Nonfunctioning T1 Pancreatic Endocrine Neoplasms

Abstract: Background: Whether patients with small (<2 cm), sporadic nonfunctioning pancreatic endocrine tumors (NF-PETs) should directly undergo pancreatic surgery or should be followed longitudinally to detect growth and malignancy still has to be defined. Study Design: Based on the pertinent literature of the past decade, a Markov model was developed to investigate this issue. In the wait-and-see strategy arm, surgery was performed if the tumor attained a size ≥2 cm or surpassed 20% of the initial size. In a Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Thus, how to best select MEN1 patients for surgery based on age, cut-off size, and/ or location remains to be formally determined. 48 There are several limitations in this systematic review and in the included studies. First, only nine studies were found to meet the criteria for this systematic review.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, how to best select MEN1 patients for surgery based on age, cut-off size, and/ or location remains to be formally determined. 48 There are several limitations in this systematic review and in the included studies. First, only nine studies were found to meet the criteria for this systematic review.…”
Section: Discussionmentioning
confidence: 97%
“…The prognosis of G1 Pan-NET was excellent for all stages and the data confirmed that non-operative management could be considered for stage I disease 21,22 . Indeed, if a conservative strategy in stage I was adopted and an earlier stage shift in stage II or III was observed, the prognosis remained good 23 . Normal lifespan probability and excess death risk histograms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, all patients with G1 and G2 Pan-NETs in stage III-IV had a significant risk of recurrence despite surgery, so an adjuvant or neoadjuvant approach might be sensible. A hypothetical shift from stage I to stage III during conservative management of small G1 neoplasms would be dangerous, but the probability of this happening is very low 23 . The G3 Pan-NET category had a RS of over 70 per cent only in stage I, suggesting that adjuvant or neoadjuvant therapy should be considered as a rational approach from stage II onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery can be considered if the patient has poor compliance or has significant concerns about long-term follow-up or tumor progression. Since elderly patients with small pNENs benefit little from surgery, active follow-up is preferred for patients over 70 years old at the first visit [48] (or over 65 years old [49] ) and those with more complications, while younger patients should be more actively treated with surgery. [50,51] However, for elderly patients with tumor progression tendency, surgery may also be actively performed to avoid a gradual decrease in surgical tolerance or a change of surgical procedure due to tumor progression.…”
Section: Question 4: What Factors Influence the Decision Of Surgery O...mentioning
confidence: 99%